Ad Libitum: centro de cuidado mental (2021)
In Colombia, various investigations have been carried out on mental illnesses and the effects they have on daily life, determining these as a major problem to be treated due to their great scope and consequences, affecting an average of 2 out of 5 people in the country . Due to this, a population analysis is made where the Caribbean area is determined as an important delimitation to be treated, determining that the most suitable place for the implementation of the architectural project is the municipality of Cartagena due to the problems of social and economic inequality, intra-family violence and nearby consequences of the armed conflict, which are triggers for the deterioration of psycho-mental conditions. For all the above, it seeks to develop a new adaptable spatial model of a psychiatric center, which supplants a large part of the Caribbean population of the country, based on the use of hybrid architectural design, mixed organic infrastructure in native wood, steel and concrete, and harmonic therapeutic spaces that adapt to the medical treatment needs, in addition to promoting the implementation of the healing architecture created by Stefan Lundin in psychiatric settings, to improve and stabilize the mind-body psycho-haptic sensations and the recovery of the patients.